(untitled) (Eurasian Journal of Ecology, 2018)
Energy Sector Development Program is conceptual and is designed as part of the strategy, implementing the program of development of Kazakhstan till 2030. Energy is the basis of development of the productive forces in any country, ensures the smooth operation of industry, agriculture, transport and municipal services. Stable economic development is impossible without the ever-evolving energy. Electricity, being one of the basic industries, plays an important role in the economic and social sphere of any state. The Kazakhstan has large reserves of energy resources and raw materials, this is a country that exports natural energy reserves. Therefore, electric power complex identified as one of the priority sectors of Kazakhstan’s economy and is regarded as a dynamically balanced system «Energy – economy – nature-society» with the sustainable development of the power industry. Electrical energy is an important, versatile, the most efficient technical and economic form of energy. The advantage of the ecological use of electricity and transmission security by power lines as compared to the fuel transportation, pumping their pipeline systems. However, electricity production at numerous power plant, thermal power plants, hydroelectric power stations, nuclear power is associated with significant adverse effects on the environment. Key words: pollutants, coal, production activities, electricity, power, power plant, Ekibastuz State District Power Plant, power unit.